2012
DOI: 10.1042/bst20120092
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation by the intrinsically disordered proteins p21 and p27

Abstract: Today, it is widely accepted that proteins that lack highly defined globular three-dimensional structures, termed IDPs (intrinsically disordered proteins), play key roles in myriad biological processes. Our understanding of how intrinsic disorder mediates biological function is, however, incomplete. In the present paper, we review disorder-mediated cell cycle regulation by two intrinsically disordered proteins, p21 and p27. A structural adaptation mechanism involving a stretchable dynamic linker helix allows p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(167 citation statements)
references
References 58 publications
5
162
0
Order By: Relevance
“…A pro-survival function of p21 in b-cells which was analogous to that demonstrated previously in the context of carcinogenesis (Yoon et al 2012) was confirmed in the pancreatic islets isolated from the w/t and p21 KO mice. The latter were found significantly more sensitive to high glucose levels with a characteristic increase in caspase activation -a clear indication of ongoing apoptosis.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…A pro-survival function of p21 in b-cells which was analogous to that demonstrated previously in the context of carcinogenesis (Yoon et al 2012) was confirmed in the pancreatic islets isolated from the w/t and p21 KO mice. The latter were found significantly more sensitive to high glucose levels with a characteristic increase in caspase activation -a clear indication of ongoing apoptosis.…”
supporting
confidence: 82%
“…For instance, it is known that p21 may act not only as a tumor suppressor but also serve as an oncogene by promoting cell growth and inhibiting apoptosis (Yoon et al 2012). Such an oncogenic function is thought to be associated with the cytoplasmic localization of p21 (Zhou et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, levels of p21 (cyclin-dependent kinase inhibitor 1 (WAF1)) and p27 (kinesin-like protein (KIP1)) proteins increased, as did apoptosis regulator BCL-2-like protein 4 (BAX) expression, whereas apoptosis regulator B-cell lymphoma 2 (BCL2) expression was reduced (69). p21 and p27 are inhibitors of cyclin-dependent kinases, hence they are involved in cellcycle control (70) and appear to suppress MCG-7 cell proliferation in vitro (71). BAX is a pro-apoptotic member of the BCL2 family and a downstream target gene of p53 that mediates p53-dependent apoptosis (72).…”
Section: Hdac Inhibitors As Anti-breast Cancer Agentsmentioning
confidence: 99%
“…Perturbations in Akt activity are associated with numerous pathologies including breast cancer (11). Akt promotes a reduction of cell cycle inhibitors such as the cyclin-dependent kinase inhibitor 1 (p21/WAF1) and p27 Kip1 and an enhancement of cell cycle proteins such as c-Myc and cyclin D1 (12). PDZ domain containing 1 (PDZK1) is a 70-kDa adapter protein expressed primarily in the apical brush-border membrane of the proximal tubules of the kidney (13) and has an important role in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%